Skin Diseases in the Immunosuppressed (Springer International Publishing, 2018)
In this book, expert dermatologists review state of the art knowledge concerning the clinical presentation and management of cutaneous diseases that develop in immunosuppressed individuals, including transplant recipients, those with primary immunodeficiencies, and HIV sufferers. Throughout the book, correlations are made with iatrogenic, primary, and acquired immunodeficiencies. A major aim is to enable dermatologists to identify the specific immunosuppressant responsible for a specific adverse effect, whether benign or malignant, in patients receiving a complex medication regimen in the setting of transplantation. Further, the book will help the dermatologist to distinguish the cutaneous adverse effects of antiviral agents from effects arising directly from advancing HIV disease. Recognition of the cutaneous manifestations of often less common primary immunodeficiencies will also be emphasized. A final goal is to improve patient outcomes by providing dermatologists with treatment strategies for skin disease arising in the immunosuppressed state. This book will be invaluable for a broad audience, from practicing dermatologists to medical and dermatology residents.